"BOSHLANG`ICH SINF O`QITUVCHILARINI AKTDAN FOYDALANISH ASOSIDA KASBIY FAOLIYATNI RIVOJLANTIRISH METODIKASINI TAKOMILLASHTIRISHNING ASOSLARI" - Gulnoza Berdiyeva (Galaxy International Interdisciplinary Research Journal, 2022)
Numerous studies have been conducted to study the problems of technology integration in education. They provide perceptual and perceived barriers to teachers ’use of technology tools in the teaching and learning process in the classroom. Thus, the main objectives of this study are to determine the perception of teachers about the use of ICT in teaching and learning in the classroom, as well as to identify problems among school teachers in the use of ICT in teaching and learning.